Temperature, but not excess of glycogen, regulates "in vitro" AMPK activity in muscle samples of steer carcasses. - Pablo Strobel; Alex Galaz; Franz Villaroel-Espíndola; Ariel Apaoblaza; Juan Carlos Slebe; Nancy Jerez-Timaure; Carmen Gallo; Alfredo Ramírez-Reveco (PLoS ONE, 2021)
Postmortem muscle temperature affects the rate of pH decline in a linear manner from 37.5°C to 0-2°C. The pH decline is correlated with the enzymatic degradation of glycogen to lactate and this process includes the metabolic coupling between glycogenolysis and glycolysis, and that are strongly upregulated by the AMPK. In this study, we used 12 samples previously characterized by have different muscle glycogen concentration, lactate and AMPK activity, selected from 38 steers that produced high final pH (>5.9) and normal final pH (<5.8) carcasses at 24 h postmortem. Moreover, we evaluated changes in the AMPK activity in samples from both categories incubated at 37, 25, 17 and 5°C and supplemented with exogenous glycogen. Finally, we analysed if there were structural differences between polymers from both categories. Our results showed that "in vitro" enzymatic AMPK activity evaluated at both 0.5 or 24 h was greater in samples from normal then high pH categories (p <0.01), and in all temperature of incubation analysed (17, 25 and 37°C). For other hand, a greater AMPK activity were obtained in samples incubated at 17 that 25 or 37°C, in normal carcasses at both 0.5 or 24 h (p < 0.01), as also in samples from carcasses categorized as high pH, but at 24 h (p < 0.05). Interestingly, AMPK activity was totally abolished at 5°C, independent of final pH category of carcasses, and was confirmed that the incubation temperature at which the maximum activity was obtained (p < 0.01), at least in carcasses with a normal pH is at 17°C. The enzymatic AMPK activity did not change in relation to excess glycogen (p > 0.05) and we did not detect structural differences in the polymers present in samples from both categories (p > 0.05), suggesting that postmortem AMPK activity may be highly sensitive to temperature and not to in vitro changes in glycogen concentration (p > 0.05). Our results allow concluding that normal concentrations of muscle glycogen immediately at the time of slaughter (0.5 h) and an adequate cooling managing of carcasses are relevant to let an efficient glycogenolytic/glycolytic flow required for lactate accumulation and pH decline, through the postmortem AMPK signalling pathway.